Arts Management Innovative Technologies in the Creative Development of Youth - Komandyshko, Elena Ph. (International Review of Management and Marketing, 2016)
The author of the article undertakes an attempt to address the issue of the creative development of studying youth within the framework of the assimilation of arts management innovative technologies. The content of the article is structured upon the basis of art and management interaction which reveals the current potential of the introduction of arts management technologies into the practice of educational institutions. The author discloses the specifics and the peculiarities of arts management technologies in the development of cultural and creative initiative of students through the example of using art project methods. The article proves that the implementation of innovative technologies is carried out on the basis of the interdisciplinary pattern and the integration of different aspects of activity, primarily the structural (organizational) and the aesthetic ones. Keywords: arts management technologies, cultural and creative initiative, an art project. JEL Classifications: M1